HUBUNGAN ANTARA ANAK SULIT MAKAN SAYURAN DENGAN PERTUMBUHAN PADA ANAK PRA SEKOLAH DI TK CENDRAWASIH KABUPATEN TANGERANG - Ria Setia Sari; Rizki Andika Saputri (Jurnal Kesehatan, 2018)
Difficult eating is the most important factor in growth in pre-school children but this problem is feared by all parents where children should eating vegetables. Things that make eating vegetables difficult is very beneficial and many of the ingredients in the vegetables . The vegetables are very useful and a lot of the content in the vegetables good for the child’s body. Aims to find out whether the realationship between children is difficult to eating vegetables with growth in pre-school children in TK Cendrawasih district Tangerang. Was to find out whether the realationship between difficult children to eating vegetables with growth in pre – school children in TK Cendrawasih district Tangerang. Used in this research is descriptive correlation with cross sectional approach where by taking data to some research variables conducted at one time (point time approach). Sample technique used by researchers is simple total sampling technique that is as much as 84 respondents. Got value of chi squre test between difficult to eat vegetables with growth that p- value 0,001 < 0,05 hence can be stated Ho rejected means there is difficult relationship of aeting vegetables with growth in pre school childred in TK Cendrawasih district Tangerang 2018. The result of this study can be recommended for futher researgh such as futher review the factors that affect difficult to eating vegetables such as parenting factorsof time of administration and psychological factors in children.